ATM withdrawals, debit card transactions at the point of sale and the demand for currency - Santiago Carbó-Valverde; Francisco Rodríguez-Fernández (SERIEs - Journal of the Spanish Economic Association, 2014)
Debit cards are employed for cash withdrawals at automated teller machines (ATMs) and for purchasing transactions at point-of-sale (POS). In this paper, we explore, for the first time to our knowledge, the determinants of debit card transaction volumes at ATM and POS, the relationship between these two alternative usages of cards and its impact on the demand for currency. We employ a unique database that considers the two-sided nature of debit cards to explore these issues. The results suggest that the intensity of the use of ATMs and POS have a large economic impact one on another. We also find a net negative effect of transactions with debit cards on the demand for currency since the positive impact of ATM usage is lower in absolute terms than the negative effect of POS volumes.
Keywords: G21; O33; L11; 330; Payment instruments; Banks; ATMs; POS; Demand for currency